Criteria weights balancing using Kemeny median - Krylovas, Aleksandras; Kosareva, Natalja (Lietuvos matematikos rinkinys, 2014)
The proposed in the article weights balancing approach enables to solve multiple criteria decision making tasks for the cases when objects are estimated by the two or more groups of the criteria which are not quantitatively compatible with each other. Criteria weights are being balanced by solving conditional optimization problems. The conditions for the certain optimization problem are determined by the construction of Kemeny median.
Keywords: multiple criteria decision making; expert assessments; weights balancing; Kemeny median